Decreased Behavioral Abnormalities After Treatment with Combined Donepezil and Yokukansankachimpihange in Alzheimer Disease: An Observational Study. The Osaki-Tajiri Project - Kenichi Meguro; Satoshi Yamaguchi (Neurology and Therapy, 2018)
Abstract Introduction Yokukansan is one of the traditional herbal medicines (Kampo medicine in Japan) commonly used in the treatment of the Behavioral and Psychological Symptoms of Dementia (BPSD). We performed an observational study using yokukansankachimpihange, which contains a nobiletin-rich Citrus reticulata, to determine whether it could improve BPSD as well as cognitive impairment in patients with Alzheimer disease (NINCDS-ADRDA). Methods Forty-six (23 vs. 23) patients were enrolled in the study sample (donepezil group vs. donepezil + yokukansankachimpihange group). The BPSD were assessed using the Frequency-Weighted Behavioral Pathology in Alzheimer Disease Rating Scale (BEHAVE-AD-FW). The Mini-Mental State Examination and the Digit Symbol test of WAIS-R were used to evaluate impairment of global cognitive function and executive function, respectively. Results No significant changes in the cognitive functions or the total BPSD scores were noted for either treatment group. Regarding the subscales of the BPSD, the subscale of Diurnal Rhythm showed a significant decrease after the treatment, and those of Affective Disturbance and Anxiety and Phobias tended to be decreased. The donepezil + yokukansankachimpihange group had a lower rate of use of anti-psychotics compared with the donepezil group, although this was not statistically significant. Conclusion These results suggest that combined treatment of yokukansankachimpihange with donepezil has a positive clinical effect on improving the behavioral abnormalities, despite the lack of any effect on cognitive functions. Improvements in the diurnal rhythm may improve affective disturbance and anxiety. Thus, yokukansankachimpihange is considered to have a mild stabilizing effect on emotion.